Investigation of Possible Effects of Melatonin Administration on Premenstrual Syndrome in Rats with a Premenstrual Syndrome Model - Sayin, Orhan; Sevindik, Elfin; Bozyil, Ahmed Sait; Pervin, Mehtap; Atli, Ayse Akmese; Kacar, Emine (Wiley, 2023)
[Abstract Not Available]
Keywords: Anxiety; Elevated t-maze test; Melatonin; Premenstrual syndrome; Rat